Child Marriage in Indonesia: The Tensions Between Statutory Law, Islamic Law, and Indigenous Cultural Practices - Maya, Mayadina Rohmi Musfiroh (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2023)
Problem statement: The increase in cases of child marriage in Indonesia has generated systemic issues from both social and economic perspectives, as well as concerning the fulfilment of children's rights. Various legal instruments have been established to prevent child marriage, including the elevation of the minimum marriage age for both men and women as stipulated in Law No. 16 of 2019, which amends Law No. 1 of 1974 concerning Marriage, alongside the enactment of the Child Protection Law and various derivative regulations. Objective: This study aims to elucidate the tension between state law, the interpretation of religious texts, and the socio-empirical practices surrounding child marriage in Indonesia, while also seeking to identify strategies to reduce child marriage rates in the country. Methods: This research employs a descriptive approach, conducting a case study in Jepara, Central Java, using qualitative data collection methods, which are analysed through the iceberg analysis model and U Theory, alongside a sociological normative framework. Results: The findings of this research are as follows: first, various policies aimed at reducing the child marriage rate in Indonesia, implemented through state laws and regulations, have proven insufficiently effective, as they have not been accompanied by strategic, implementable, cross-sectoral, and sectoral policies and programmes. Second, religious texts pertaining to the minimum marriage age are not explicitly defined within Islamic law, leading to diverse interpretations; these texts tend to be understood in a textual rather than contextual manner. The tension among the three legal axes (positive law, religious law, and customary law) has contributed to the perception among certain members of the public, religious leaders, and government officials that child marriage retains a degree of legitimacy within Islamic law. Conclusion: Strategies to reduce child marriage in Indonesia must be developed in a comprehensive, integrative, collaborative, and cross-sectoral manner, involving all stakeholders, including the executive, legislature, judiciary, youth groups, parents, religious leaders, community leaders, teachers, and educational institutions.